Mandibular premolars with unusual root canal configuration: A report of two cases - Sarah Abdulla Essa Al-Mahroos; Abdullah Ali Al-Sharif; Ibrahim Ali Ahmad (Wolters Kluwer Medknow Publications, 2016)
Knowledge of the normal root canal morphology and its variation is essential to ensure a successful root canal therapy. The aim of this report is to describe the endodontic treatment of two mandibular premolars with aberrant root canal morphology with the aid of dental operating microscope. A 29-year-old Saudi male with three mandibular left premolars was referred by the Prosthodontic Department for endodontic evaluation prior to placement of final coronal restorations. The first premolar was diagnosed as having necrotic pulp while the third premolar was previously treated. Root canal treatment and nonsurgical root canal retreatment were performed for the first and third premolars, respectively. The first premolar had a C-shaped configuration and Vertucci's Type V (1-2) canal system while the third premolar had Type III configuration (1-2-1). One year later, the teeth were asymptomatic with normal periapical tissues radiographically. Root canal aberrations may occur in any tooth type, and the clinicians should always assume the presence of these aberrations and use all the available tools to detect and manage them.